The water yield of Molawin watershed as influenced by rainfall, physiographic and anthropogenic factors - Pasa, Arturo E.; Villanueva, Teodoro R. (Annals of Tropical Research, 1998)
A study was conducted to determine the effects of rainfall, physiographic and anthropogenic factors on the water yield of Molawin watershed. Results showed that the total suspended solids was increased by the tractive force of streamflow and the activities of the people inside the watershed. Rainfall increased the streamflow volume but showed delayed response in the later part of the study. The volcanic mud spring also decreased the water quality on the upper portion of the watershed. The emission of grayish mud from the mud spring caused high total suspended solids and turbidity of the river water. This natural condition could have also caused the low pH and chemical oxygen demand of water at the fifth station. The lower portion of the watershed, on the other hand, showed low dissolved oxygen but with high chemical and biological oxygen demands. This study concluded that the continued influx of people into the watershed would further degrade the water quality and could cause unwanted streamflow fluctuations. Maintaining the present vegetation and controlling human activities are recommended.